Fake news and disinformation in Southeast Asia: how should ASEAN respond? - Putra, Bama Andika (Frontiers in Communication, 2024)
Southeast Asian nations are vulnerable to fake news and disinformation due to the lack of digital literacy, growing dependence upon online platforms, and the non-democratic nature of ASEAN member states; ASEAN has agreed in the past years to decide, at the normative level, the importance of countering fake news and disinformation. However, it lacks a collective, regional approach; ASEAN needs to define what fake news and disinformation consist of, elevation to a non-traditional security threat, and establishment of an ASEAN-centered fast-checking network as feasible policy options to counter fake news and disinformation in the region; Special attention is needed to consider ASEAN's philosophical foundations of non-interference, non-intervention, and respect for sovereignty, which allows state practices of surveillance, legal prosecutions, firewalls, and censorships to be maintained